INFLUENCE OF ORGANIZATIONAL COMMUNICATION ON EMPLOYEE COMMITMENT AMONG BANK EMPLOYEES IN KERALA - Badisha V; Anilkumar M; Jincy V. K; Hamsa E; Kavitha V. K (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study investigates the influence of organizational communication on employee commitment among bank employees in Kerala. Data collected from 144 employees including officers and clerical staff from three public and three private sector banks in Kerala, using a structured questionnaire. The reliability of test instrument was done using Cronbach’s Alpha which shed that all constructs in the study showed acceptable reliability (α > 0.7). Pearson correlation analysis revealed a strong, positive relationship between organizational communication and employee commitment (r = .691, p < .01). Multiple regression analysis showed that upward communication opportunities, supportive climate, and quality of information significantly impacted commitment, collectively explaining 49.1% of the variance (R² = .491, p < .001). Among the predictors, upward communication opportunity exerted the strongest positive influence. T-tests and ANOVA results indicated that gender significantly affected both organizational communications. These findings emphasize the critical role of transparent and participative communication practices in enhancing employee commitment in the banking sector.